High ferritin levels have major effects on the morphology of erythrocytes in Alzheimer's disease - Bester, Janette; Buys, Antoinette; Lipinski, Boguslaw; Kell, Douglas B.; Pretorius, Etheresia (Frontiers in Aging Neuroscience, 2013)
Introduction: Unliganded iron both contributes to the pathology of Alzheimer’s disease (AD) and also changes the morphology of erythrocytes (RBCs). We tested the hypothesis that these two facts might be linked, i.e. that the RBCs of AD individuals have a variant morphology, that might have diagnostic or prognostic value. Methods: We included a literature survey of AD and its relationships to the vascular system, followed by a laboratory study. Four different microscopy techniques were used and results statistically compared to analyze trends between high and normal serum ferritin (SF) AD individuals. Results: Light and scanning electron microscopies showed little difference between the morphologies of RBCs taken from healthy individuals and from normal SF AD individuals. By contrast, there were substantial changes in the morphology of RBCs taken from high SF AD individuals. These differences were also observed using confocal microscopy and as a significantly greater membrane stiffness (measured using force-distance curves). Conclusion: We argue that high ferritin levels may contribute to an accelerated pathology in AD. Our findings reinforce the importance of (unliganded) iron in AD, and suggest the possibility both of an early diagnosis and some means of treating or slowing down the progress of this disease.